Bijak Dan Cerdas Bersosial Media Di Era Keterbukaan Informasi Di Desa Simanindo Kecamatan Simanindo Kabupaten Samosir - Sartana; Maranata Pasaribu; Sariadin Siallagan; Fauzi Haris Simbolon; Jaidup Banjarnahor (Universitas Mandiri Bina Prestasi (UMBP), 2024)
In today's era of open information, society's need for information is increasingly urgent and important. This encourages various elements of society to demand their basic rights, especially the right to obtain information. The public's need for information is a basic right for every person in order to develop their personal qualities and in order to live their social life. Social media or what is also known as social networking is part of new media. It is clear that the interactive content in new media is very high, thus allowing a lot of misuse in conveying information and messages which results in misinformation among fellow social media users and even gives rise to misguided understandings (hoaxes) and hate speech. For this reason, policy and intelligence are needed in using social media so that the information sent and received is quality information and not misleading. By carrying out socialization and counseling wisely and intelligently using social media among the community, it is hoped that it can help the community (especially in Simanindo Village, Simanindo sub-district, Samosir Regency) in using good, healthy and high-quality social media.